2015
DOI: 10.1021/acs.cgd.5b00479
|View full text |Cite
|
Sign up to set email alerts
|

Process Intensification through Continuous Spherical Crystallization Using a Two-Stage Mixed Suspension Mixed Product Removal (MSMPR) System

Abstract: Of utmost importance in the crystallization of active pharmaceutical ingredients (APIs) in the pharmaceutical industry is to produce crystals of good physical, processing, and biopharmaceutical properties. The definition of good physical properties depends on what the end goal and the drug formulation that the crystals will be a part of, but often processing and biopharmaceutical properties are competing interests. In most cases, the crystallization process is tailored to improve downstream process efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…It has been shown that there is a critical range for the BSR. Below this range, there is no significant agglomeration, and above this range a paste-like product is produced [55,56]. Only within this range is the agglomeration process efficient.…”
Section: Effect Of the Amount Of Bridging Liquidmentioning
confidence: 99%
“…It has been shown that there is a critical range for the BSR. Below this range, there is no significant agglomeration, and above this range a paste-like product is produced [55,56]. Only within this range is the agglomeration process efficient.…”
Section: Effect Of the Amount Of Bridging Liquidmentioning
confidence: 99%
“…By imposing this oscillatory turbulence, OFBRs do not need to operate at high throughput flow rates like PFRs, meaning smaller tube lengths and holdup volumes. However, several authors have indicated that these oscillations have a significant impact on the RTD of the system, 2,4,5,6 but do not consider system geometry or scale up. Herein, two commercial systems of different geometry and scale will be evaluated under a variety of operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Further flexibility could be achieved by introducing individual motors to control the oscillation conditions in each vessel which may be beneficial for example in controlling the size of agglomerate in spherical agglomeration processing. [68][69][70]…”
Section: Continuous Cooling Crystallisation Of Pcmmentioning
confidence: 99%